Construction of Holographic Immersion Chamber Based on Multisource Information Fusion and Interactive Virtual Reality Technology. (18th July 2022) - Wang, Chunying; Liu, Yin
Abstract : Nowadays, many visual artists actively respond to the drastic changes taking place in today's society, build a communication bridge between real places and virtual places, and use holographic image technology to organically integrate them with each other. We are increasingly shuttling through the network of unbounded space. These spaces have no fixed geographical location. With the help of modern science and technology, they often fall into the field of vision of the viewer. With the development of the times, virtual reality technology is a computer simulation system that can create and experience the virtual world. It mainly uses computers to generate a simulated environment. It is a multisource information fusion interactive virtual reality technology to help users immerse themselves in the virtual environment. This paper studies the holographic immersion chamber based on multisource information fusion interactive virtual reality technology. The approximation index of the transformation matrix calculated by the registration algorithm based on SIFT+MSA is 1.7073, which is less than 4.0017 obtained by SIFT matching algorithm. It can be seen that the error of CCD image registration parameters calculated by this algorithm is smaller. In the process of the development of multisource information fusion interactive virtual reality technology, the technical feature of virtual reality is gradually integrated into the user and application object, becoming more closely connected and finally causing the user of the technology the feeling of "immersion" in the use experience.